2020
DOI: 10.15252/embr.202050642
|View full text |Cite
|
Sign up to set email alerts
|

NEDD4L‐mediated Merlin ubiquitination facilitates Hippo pathway activation

Abstract: The tumor suppressor Merlin/NF2, a key activator of the Hippo pathway in growth control, is regulated by phosphorylation. However, it is uncertain whether additional post-translational modifications regulate Merlin. Here, we show that ubiquitination is required to activate Merlin in the Hippo pathway. Ubiquitinated Merlin is mostly conjugated by one or two ubiquitin molecules. Such modification is promoted by serine 518 dephosphorylation in response to Ca 2+ signaling or cell detachment. Merlin ubiquitination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Besides PKC, an E3 ubiquitin ligase, neural precursor cell-expressed developmentally downregulated protein four like (NEDD4L) could be another Ca 2+ effector in the Hippo pathway regulation. Recently, Wei et al, found that elevation of intracellular Ca 2+ level or loss of matrix attachment in human glioblastoma cells and mouse Schwann cells triggers ubiquitination of Merlin ( Wei et al, 2020 ), an essential component in the Hippo pathway for Lats1/2 activation. This process is mediated by NEDD4L and a scaffold protein, AMOTL1 ( Figure 1 ).…”
Section: Mechanism Of the Hippo Pathway Regulation By Ca 2+ And Actin Cytoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides PKC, an E3 ubiquitin ligase, neural precursor cell-expressed developmentally downregulated protein four like (NEDD4L) could be another Ca 2+ effector in the Hippo pathway regulation. Recently, Wei et al, found that elevation of intracellular Ca 2+ level or loss of matrix attachment in human glioblastoma cells and mouse Schwann cells triggers ubiquitination of Merlin ( Wei et al, 2020 ), an essential component in the Hippo pathway for Lats1/2 activation. This process is mediated by NEDD4L and a scaffold protein, AMOTL1 ( Figure 1 ).…”
Section: Mechanism Of the Hippo Pathway Regulation By Ca 2+ And Actin Cytoskeletonmentioning
confidence: 99%
“…The ubiquitination is required for Merlin to interact and activate Lats1 in response to upstream signals, including Ca 2+ . Because Merlin-Lats1/2 interaction is important for Lats1/2 activation ( Yin et al, 2013 ), Merlin ubiquitination appears to promote Lats1 activation through facilitating the interaction between Merlin and Lats1 ( Wei et al, 2020 ). Currently, it is still unclear how Merlin ubiquitination can promote its interaction with Lats1.…”
Section: Mechanism Of the Hippo Pathway Regulation By Ca 2+ And Actin Cytoskeletonmentioning
confidence: 99%
“…These results suggested that INHBA may downregulate Merlin levels via post-translational modification. Previous studies have confirmed that the intracellular regulatory function of Merlin is lost via ubiquitination-mediated degradation (36,37); however, as a member of the TGF-β superfamily, INHBA itself has no ubiquitination function. Mota et al (38) confirmed that Merlin expression was associated with Smad7.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast to phosphorylation at S518, Merlin phosphorylated at S10, T230, and/or S315 is subject to ubiquitination and proteasome-mediated degradation ( Laulajainen et al, 2011 ), which, however, requires S518 to be dephosphorylated ( Li et al, 2015 ; Wei et al, 2020 ), suggesting that Merlin phosphorylated at S518 and Merlin phosphorylated at S10, T230, and/or S315 are two functionally exclusive states ( Figure 4D ). Merlin ubiquitination is mediated by the E3 ubiquitin ligase, neural precursor cell expressed developmentally downregulated protein 4 (NEDD4), which conjugates one or two ubiquitin molecules at Merlin K396 and K159 by the aid of AMOT ( Wei et al, 2020 ). In this process, AMOT serves as a scaffold protein to bind to Merlin through their mutual coiled-coil domains ( Yi et al, 2011 ; Li et al, 2015 ) and bind to NEDD4 through the association of its two PPXY motifs with the WW domains of NEDD4 ( Skouloudaki and Walz, 2012 ).…”
Section: Supporting Boxesmentioning
confidence: 99%